Reconstruction of massive tibial bone and soft tissue defects by trifocal bone transport combined with soft tissue distraction: experience from 31 cases - Yong-Qing Xu; Xin-Yu Fan; Xiao-Qing He; Hong-Jie Wen (BMC Musculoskeletal Disorders, 2021)
Abstract Background Large post-traumatic tibial bone defects combined with soft tissue defects are a common orthopedic clinical problem associated with poor outcomes when treated using traditional surgical methods. The study was designed to investigate the safety and efficacy of trifocal bone transport (TFT) and soft-tissue transport with the Ilizarov technique for large posttraumatic tibial bone and soft tissue defects. Methods We retrospectively reviewed 31 patients with massive posttraumatic tibial bone and soft tissue defects from May 2009 to May 2016. All of the eligible patients were managed by TFT and soft-tissue transport. The median age was 33.4 years (range, 2–58 years). The mean defect of bone was 11.87 cm ± 2.78 cm (range, 8.2–18.2 cm) after radical resection performed by TFT. The soft tissue defects ranged from 7 cm × 8 cm to 24 cm × 12 cm. The observed results included bone union time, wound close time and true complications. The Association for the Study and Application of the Method of Ilizarov (ASAMI) scoring system was used to assess bone and functional results and postoperative complications were evaluated by Paley classification. Results The mean duration of follow-up after frame removal was 32 months (range, 12–96 months). All cases achieved complete union in both the elongation sites and the docking sites, and eradication of infection. The mean bone transport time was 94.04 ± 23.33 days (range, 63.7–147 days). The mean external fixation time was 22.74 ± 6.82 months (range, 14–37 months), and the mean external fixation index (EFI) was 1.91 ± 0.3 months/cm (range, 1.2–2.5 months/cm). The bone results were excellent in 6 patients, good in 14 patients, fair in 8 patients and poor in 3 patients. The functional results were excellent in 8 patients, good in 15 patients, fair in 5 patients and poor in 3 patients. Conclusion: TFT, in conjunction with soft tissue transport technique, can give good results in most patients (in this article, good and excellent results were observed in 64% of patients). Soft tissue transport is a feasible method in providing good soft tissue coverage on the bone ends. Although it has no advantages over microvascular techniques, it might be an good alternative in the absence of an experienced flap surgeon. Nonetheless, high-quality controlled studies are needed to assess its long-term safety and efficacy.